The incidence and prevalence of epilepsy in the United Kingdom 2013–2018: A retrospective cohort study of UK primary care data. (February 2023) - Wigglesworth, S; Neligan, A; Dickson, JM; Pullen, A; Yelland, E; Anjuman, T; Reuber, M
Highlights: In the UK, the estimated overall point prevalence for epilepsy was 9.37 per 1000 persons. The overall estimated incidence rate was 42.68 per 100, 000 person-years. In England, the estimated incidence, 37.41 per 100, 000 person-years and prevalence, 8.85 per 1000 persons was lower compared to figures for Scotland, Wales and Northern Ireland. Abstract: Purpose: The aim of this study was to update overall incidence and prevalence calculations for epilepsy of the United Kingdom (UK) and its constituent nations (England, Northern Ireland, Scotland, and Wales). Methods: We used data from primary care practices contributing to the Clinical Practice Research Datalink (CRPD), based on the electronic health records of 14 million patients, representing approximately 20% of the population. CPRD contains data from two different health record systems: the Vision clinical system (CPRD GOLD database) and the EMIS Web® clinical system (CPRD Aurum database). We calculated incidence and prevalence rates with 95% confidence intervals (CIs). Data were stratified by age, gender, deprivation, country (England, Scotland, Wales and Northern Ireland) and region (England only). Results: In the UK, the estimated overall point prevalence for epilepsy was 9.37 per 1000 persons / year (95% CI 9.34–9.40) and the overall estimated incidence rate was 42.68 per 100, 000 person-years (95% 42.18–43.18) using the CPRD GOLD database. In England, the estimated incidence (37.41 (95% CI 36.96–37.83)) and prevalence (8.85 (95% CI 8.83–8.87)) was lower (combined databases) compared to figures for Scotland (incidence 47.76 (95% CI 46.15–49.42)); prevalence 10.13 (95% CI 10.06–10.20)) (CPRD GOLD only), Wales (incidence 54.84 (95% CI 52.79–56.95); prevalence 11.40 (95% CI 11.31–11.49)) (CPRD GOLD only) and Northern Ireland (incidence 46.18 (95% CI 43.13–49.90); prevalence 12.08 (95% CI 11.93–12.23))(combined databases). Prevalence and incidence were higher in more deprived regions. Conclusion: The prevalence and incidence of epilepsy in the UK is broadly in line with other high income countries, showing the usual pattern of high incidence in the young and the old, with a nadir in middle age. The prevalence of epilepsy has fallen slightly since 2011. There is significant geographical variation (between countries and between regions), and a suggestion of a relationship between deprivation and epilepsy which needs further investigation.